NRAS mutations in cutaneous T cell lymphoma (CTCL) sensitize tumors towards treatment with the multikinase inhibitor Sorafenib - Kießling, Michael; Nicolay, Jan Peter; Schlör, Tabea; Klemke, Claus-Detlev (OncoTarget, 2017)
Therapy of cutaneous T cell lymphoma (CTCL) is complicated by a distinct resistance of the malignant T cells towards apoptosis that can be caused by NRAS mutations in late-stage patients. These mutations correlate with decreased overall survival, but sensitize the respective CTCL cells towards MEK-inhibition-induced apoptosis which represents a promising novel therapeutic target in CTCL. Here, we show that the multi-kinase inhibitor Sorafenib induces apoptosis in NRAS-mutated CTCL cells. CTCL cell lines and to a minor extent primary T cells from Sézary patients without NRAS mutations are also affected by Sorafenib-induced apoptosis suggesting a sensitizing role of NRAS mutations for Sorafenib-induced apoptosis. When combining Sorafenib with the established CTCL medication Vorinostat we detected an increase in cell death sensitivity in CTCL cells. The combination treatment acted synergistically in apoptosis induction in both non-mutant and mutant CTCL cells. Mechanistically, this synergistic apoptosis induction by Sorafenib and Vorinostat is based on the downregulation of the anti-apoptotic protein Mcl-1, but not of other Bcl-2 family members. Taken together, these findings suggest that Sorafenib in combination with Vorinostat represents a novel therapeutic approach for the treatment of CTCL patients.